Hemodynamic Changes During Physiological and Pharmacological Stress Testing in Healthy Subjects, Aortic Stenosis and Aortic Coarctation Patients–A Systematic Review and Meta-Analysis - Runte, Kilian; Brosien, Kay; Salcher-Konrad, Maximilian; Schubert, Charlotte; Goubergrits, Leonid; Kelle, Sebastian; Schubert, Stephan; Berger, Felix; Kuehne, Titus; Kelm, Marcus (Frontiers in Cardiovascular Medicine, 2019)
Introduction: Exercise testing has become a diagnostic standard in the evaluation and management of heart disease. While different methods of exercise and pharmacological stress testing exist, only little is known about their comparability. We aimed to assess hemodynamic changes during dynamic exercise, isometric exercise and dobutamine stress testing at different stress intensities in healthy subjects and patients with aortic stenosis (AS) and aortic coarctation (CoA). Methods: A systematic literature search (PROSPERO 2017:CRD42017078608) in MEDLINE of interventional trials was conducted to identify eligible studies providing evidence of changes in hemodynamic parameters under different stress conditions acquired by MRI or echocardiography. A random effects model was used to estimate pooled mean changes in hemodynamics. Results: 128 study arms with a total of 3139 stress-examinations were included. In healthy subjects / (where available) in AS, pooled mean changes (95% CIs) during light dynamic stress were 31.78 (27.82-35.74)bpm in heart rate (HR) and 6.59 (2.58-10.61)ml in stroke volume (SV). Changes during light pharmacological stress were 13.71 (7.87-19.56)/14.0 (9.82-18.18)bpm in HR and 5.47 (0.3-10.63)/8.0 (3.82-12.18)ml in SV. Changes during light isometric stress were 18.44 (10.74-26.14)/5.0 (-1.17-11.17)bpm in HR and -4.17 (-14.37-6.03)/-4.0 (-16.43-8.43)ml in SV. Changes during moderate dynamic stress were 49.57 (40.03-59.1)/46.45 (42.63-50.27)bpm in HR and 11.64 (5.87-17.42)ml in SV. During moderate pharmacological stress changes in HR were 42.83 (36.94-48.72)/18.66 (2.38-34.93)bpm and in SV 6.29 (-2.0-14.58)/13.11 (7.99-18.23)ml. During high intensity dynamic stress changes in HR were 89.31 (81.46-97.17)/55.32 (47.31-63.33)bpm and in SV 21.31 (13.42-29.21)/-0.96 (-5.27-3.35)ml. During high pharmacological stress changes in HR were 53.58 (36.53-70.64)/42.52 (32.77-52.28)bpm and in SV 0.98 (-9.32-11.27)/14.06 (-1.62-29.74)ml. HR increase and age were inversely correlated at high stress intensities. In CoA, evidence was limited to single studies. Conclusion: This systematic review and meta-analysis presents pooled hemodynamic changes under light, moderate and high intensity exercise and pharmacological stress, while considering the potential influence of age. Despite limited availability of comparative studies, the reference values presented in this review allow estimation of the expected individual range of a circulatory response in healthy individuals and patients with AS and may contribute to future study planning and patient-specific models even when stress testing is contraindicated.